Additives for soluble liquid crystal polymer solutions
A soluble liquid crystal polymer solution with additives addresses mechanical anisotropy and warping issues by forming a composite layer with reduced thermal expansion, ensuring mechanical stability and high-frequency circuit integrity.
Patent Information
- Application Number
- JP2021029098
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-09-14
- Filing Date
- 2021-02-25
- Publication Date
- 2025-01-06
- Estimated Expiration
- 2038-03-23
AI Technical Summary
Conventional liquid crystal polymer films used for high-frequency substrates exhibit mechanical anisotropy and reduced strength in the transverse direction, leading to difficulties in controlling molecular chain orientation and environmental parameters, which worsens as laminate thickness decreases, causing warping and decreased strength.
A soluble liquid crystal polymer solution containing additives such as aromatic polymers and inorganic fillers is used to form a composite layer with reduced thermal expansion, improving mechanical properties and stability.
The composite layer reduces thermal expansion, enhancing mechanical strength and stability, preventing warping, and maintaining high-frequency circuit performance.
Smart Images

Figure 0007607912000004 
Figure 0007607912000001 
Figure 0007607912000002
Abstract
Description
[Technical field]
[0001] The present invention relates to soluble Liquid Crystal Polymer Solution Additives Regarding. [Background technology]
[0002] Strong and high-speed signal transmission is required to meet the multi-functional market demands of 3C mobile communication products. Flexible printed circuit (FPC) structures need to be thinner and shorter. In recent years, functionally, the communication frequencies of electronic devices such as smartphones and tablet computers operate at high bands, and the operating frequencies between each wireless communication module range from low frequencies of several MHz to high frequencies of several GHz. To meet the demands of high-frequency circuits, it is necessary to reduce the adverse effects of resistive delay (RC delay) in conventional mobile devices. Summary of the Invention [Problem to be solved by the invention]
[0003] Generally, liquid crystal polymer films used for high frequency substrates are formed from liquid crystal polymer particles by hot melt extrusion, inflation molding, or blow molding. The orientation of the molecular chains affects the construction of mechanical properties due to the molecular orientation caused by the shear flow and the liquid crystal nature of the extensional flow when the liquid crystal polymer melts, so the mechanical properties change depending on the conditions for forming the molecular chain orientation in the molded body. That is, the conditions for molecular chain orientation due to the flow during molding and the conditions for maintaining the orientation during cooling and solidification both affect the formed mechanical properties. Conventionally, aromatic liquid crystal polyester films formed by extrusion molding have weaker mechanical properties in the transverse direction (TD) than in the machine direction (MD), that is, they have large anisotropy. That is, such processes require control of many environmental parameters to adjust the crystal arrangement of the molecular chains and avoid deterioration of the mechanical properties, making the process more difficult. In addition, as the thickness of the laminate becomes thinner, the strength of the laminate decreases and the warping of the laminate increases. [Means for solving the problem]
[0004] One aspect of the present invention is An additive for a soluble liquid crystal polymer solution, comprising the soluble liquid crystal polymer The present invention includes a liquid crystal polymer and an aromatic polymer, the liquid crystal polymer being composed of the following repeating units: The structure is [ka] (Ar is 1,4-phenylene, 1,3-phenylene ,3-phenylene), 2,6-naphthalene or 4,4'-biphenylene, Y is O or NH, Z is C=O, and X is amino, carboxamide, oxamido, imido or imino, amidino , aminocarbonylamino, aminothiocal aminothiocarbonyl, aminocarbonyloxy carbonyloxy), aminosulfonyl, amino Sulfonyloxy (aminosulfonyloxy), aminosulfonylamino (a minosulfonylamino, carboxyl ester ster), (alkoxycarbonyl)oxy y), or a combination thereof) The additive of the soluble liquid crystal polymer solution is an organic polymer or an inorganic filler, The composition is a solution in which 100 parts by weight of the soluble liquid crystal polymer is dissolved, and the amount of the soluble liquid crystal polymer is 1 to 300 parts by weight. When the liquid crystal polymer composite layer is formed by applying the solution to a substrate, A polymerizable liquid crystal composite layer having a thermal expansion coefficient that is reduced. Additives for soluble liquid crystal polymer solutions to provide.
[0005] According to one or more embodiments of the present invention, the additive is an organic polymer selected from the group consisting of polyester liquid crystal polymers, aromatic polyesters, aromatic polyamides, polyparaphenylene terephthalamides, polyparaphenylene benzobisoxazoles, and copolymers of p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid.
[0006] According to one or more embodiments of the present invention, The organic polymer is the soluble liquid crystal polymer. The organic polymer is insoluble in the solvent of the solution, and has an average particle size of 0.1 to 20 μm. .
[0007] According to one or more embodiments of the present invention, Additives are BN and Al. 2 O 3 , AlN, T iO 2 , SiO 2 and combinations thereof. .
[0008] According to one or more embodiments of the present invention, The average particle size of the inorganic filler is 0.1 to 20 in μm .
[0009] According to one or more embodiments of the present invention, the inorganic filler has an average particle size of 0.1 to 20 μm.
[0010] According to one or more embodiments of the present invention, the additive is 1 to 300 parts by weight based on 100 parts by weight of the soluble liquid crystal polymer.
[0011] According to one or more embodiments of the present invention, the solvent is selected from the group consisting of N-methyl-2-pyrrolidone, N,N-dimethylacetamide, γ-butyrolactone, dimethylformamide, ethylene glycol monobutyl ether and ethylene glycol monoethyl ether.
[0012] One aspect of the present invention provides a high frequency composite substrate comprising a metal layer and a liquid crystal polymer composite layer made of the liquid crystal polymer composition of any one of the above embodiments.
[0013] According to one or more embodiments of the invention, the metal layer comprises copper, aluminum, iron, silver, palladium, nickel, chromium, molybdenum, tungsten, zinc, chromium, manganese, cobalt, gold, tin, lead, stainless steel or an alloy of these metals. [Brief description of the drawings]
[0014] In order to make the above and other objects, features and advantages of the present invention more comprehensible, the present invention will be described in detail below in conjunction with the accompanying drawings. [Figure 1] 1 illustrates a laminate according to some embodiments of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] For a more detailed and complete description of the present invention, reference may be made to the accompanying drawings and various embodiments described below.
[0016] As used herein, singular terms include plural referents unless the context clearly dictates otherwise. By reference to a particular designation, such as "in one embodiment," a particular feature, structure, or characteristic is shown in at least one embodiment of the present disclosure. Thus, when a term such as "in one embodiment" appears as a specific designation, it does not necessarily refer to the same embodiment, and furthermore, the particular features, structures, or characteristics can be combined in one or more embodiments as appropriate under the circumstances.
[0017] FIG. 1 shows a laminate 100 including a metal layer 110 and a liquid crystal polymer composite layer 120. The laminate 100 may be, for example, a high-frequency composite substrate applicable to high-frequency high-speed transmission. The liquid crystal polymer composite layer 120 is disposed on the metal layer 110. In an embodiment, the liquid crystal polymer composite layer 120 directly contacts the metal layer 110. In an embodiment, the metal layer 110 may include a layer made of copper, aluminum, iron, silver, palladium, nickel, chromium, molybdenum, tungsten, zinc, chromium, manganese, cobalt, gold, tin, lead, stainless steel, or an alloy of these metals. In an embodiment, the roughness of the contact surface between the metal layer 110 and the liquid crystal polymer composite layer 120 is about 0.2 μm to about 5 μm, for example, about 0.5 μm, 1 μm, 2 μm, or 4 μm. In another embodiment, the metal layer 110 may be a copper foil, such as, for example, an electrodeposited copper foil or a rolled copper foil.
[0018] The laminate 100 may be flexible or rigid. A flexible laminate 100 may be, for example, a flex copper clad laminate (FCCL) and may be used to manufacture a flexible circuit board (FCB). A rigid laminate 100 may be, for example, a copper clad laminate (CCL) and may be used to manufacture a rigid circuit board. The rigid circuit may be a printed circuit board (PCB).
[0019] In some embodiments of the present disclosure, the laminate 100 further includes an adhesive layer (not shown) located between the metal layer 110 and the liquid crystal polymer composite layer 120. The adhesive layer is used to bond the metal layer 110 and the liquid crystal polymer composite layer 120. The adhesive layer may be made of epoxy resin, phenoxy resin, acrylic resin, ethyl carbamate resin, polymerized siloxanes, poly-p-xylene resin, liquid crystal polymer, bismaleimide resin, polyimide resin, or a combination thereof. It should be noted that in other embodiments of the present disclosure, the adhesive layer may be omitted, i.e., the liquid crystal polymer composite layer 120 and the metal layer 110 may be in direct contact with each other.
[0020] In one embodiment of the present disclosure, the liquid crystal polymer composite layer 120 is made of a liquid crystal polymer (LCP) composition or other suitable materials. The liquid crystal polymer has a closely packed linear polymer structure, so that the resulting product has good mechanical properties and can exhibit high strength or high heat resistance through processing orientation, and is suitable for use in heat-resistant electronic materials and high-performance engineering plastic substrates.
[0021] In some embodiments, the liquid crystal polymer composite layer 120 may be formed alone without forming on the metal layer 110, and may be directly used as a dielectric layer or an insulating layer. That is, the laminate 100 may be formed without the metal layer 110 and the adhesive layer (not shown). Therefore, the formation of the liquid crystal polymer composite layer 120 is not limited to contacting the metal layer 110.
[0022] Liquid crystal polymers are easily arranged to become molecular barriers, so they have a low water absorption rate and a high gas barrier effect. Films formed from liquid crystal polymers have a lower water absorption rate, dielectric constant, and coefficient of thermal expansion (CTE) than conventional polyimide (PI) film materials, as well as good dimensional stability, gas barrier properties, and thermal conductivity. In particular, the linear thermal expansion coefficient in the flow direction is one order of magnitude smaller than that of ordinary plastics and is close to that of metals. Liquid crystal polymers have recyclable material properties and can be directly thermally bonded to metal layers without using adhesives such as epoxy resin gums, making them more cost-effective. In addition, since there is no need to use adhesives for bonding, the glass transition temperature (Tg) due to adhesive residues is not high enough, and there is no problem of secondary coating adhesive hardening.
[0023] Since the liquid crystal polymer composite layer 120 contains a liquid crystal polymer having a low dielectric constant, for example, between 2 and 4, the capacitance of the laminate 100 can be reduced, and the capacitance, for example, parasitic capacitance, of a circuit board manufactured with the laminate 100 can be reduced. In this way, the adverse effect of resistance delay can be reduced to meet the requirements of high frequency circuits. In addition, since the liquid crystal polymer composite layer 120 manufactured from the liquid crystal polymer has a chlorine (Cl), lithium (Li), and sodium (Na) content of less than 1 ppm, the purity of the liquid crystal polymer is high, and it is suitable for use in precision electronic products.
[0024] Generally, in the processing of liquid crystal polymer, liquid crystal polymer particles are mainly used by hot melt extrusion, inflation molding or blow molding.As mentioned above, many parameters need to be controlled in the process to control molecular crystal arrangement, which increases the difficulty of processing.
[0025] In order to improve the above-mentioned shortcomings of hot-melt liquid crystal polymer, the inventors have studied how to modify the liquid crystal polymer, make the modified liquid crystal polymer soluble in an organic solvent, and coat the modified liquid crystal polymer solution to form a liquid crystal polymer layer, thereby reducing the difficulty of the process. However, the inventors have found that the thermal expansion coefficient of the modified liquid crystal polymer increases due to the change in the polymer configuration and processing method. If a laminate is made using a material with a too high thermal expansion coefficient as the liquid crystal polymer composite layer, the stability of the laminate in use will be affected, for example, warping of the boat will occur.
[0026] The liquid crystal polymer composition provided in the present disclosure can improve the above-mentioned problem of the excessively high thermal expansion coefficient. In an embodiment of the present disclosure, the liquid crystal polymer composite layer 120 is manufactured with the liquid crystal polymer composition. The liquid crystal polymer composition includes a solvent, a soluble liquid crystal polymer, and an additive.
[0027] In an embodiment, the modified liquid crystal polymer is a soluble liquid crystal polymer that can be dissolved in a solvent, such as N-methyl-2-pyrrolidone (NMP), N,N-dimethylacetamide (DMAC), gamma-butyrolactone (GBL), dimethylformamide (DMF), ethylene glycol monobutyl ether (2-butoxyethanol), or ethylene glycol monoethyl ether (2-ethyloxyethanol).
[0028] In some embodiments, the soluble liquid crystal polymer comprises a liquid crystal polymer and an aromatic polymer, the aromatic polymer being selected from one or more of aromatic polyester, aromatic polyamide, poly(p-phenylene terephthalamide; PPTA), poly(p-phenylene-2,6-benzobisoxazole; PBO), and poly(p-hydroxybenzoic acid-co-2-hydroxy-6-naphthoic acid).
[0029] In one embodiment, the liquid crystal polymer in the soluble liquid crystal polymer is [ka] (Ar may be 1,4-phenylene, 1,3-phenylene, 2,6-naphthalene or 4,4'-biphenylene, Y may be O or NH, Z is C=O and X is amino, carboxamido, imido or imino, amidino, aminocarbonylamino, aminothiocarbonyl, aminocarbonyloxy, aminosulfonyl, aminosulfonyloxy, aminosulfonylamino, carboxyl ester, (carboxyl ester)amino ... The repeating unit structure of the soluble liquid crystal polymer may be, but is not limited to, (ester)amino, (alkoxycarbonyl)oxy, alkoxycarbonyl, hydroxyamino, alkoxyamino, cyanato, isocyanato, or a combination thereof. In the above solvent, the solubility of the soluble liquid crystal polymer is higher than that of ordinary liquid crystal polymers.
[0030] The liquid crystal polymer composite layer 120 manufactured from a liquid crystal polymer or a liquid crystal polymer composition containing a soluble liquid crystal polymer is suitable for use as a substrate for a flexible printed circuit (FPC), an interposer between a tape ball grid array (TBGA) and a chip scale package (CSP), a high-density multi-layer board, a high-frequency board, an insulating film / tape for IC packaging, a carrier film and an adhesive film for tape automated bonding (TAB), and high-heat engineering plastics.
[0031] The additives in the liquid crystalline polymer composition may be, for example, organic polymers, inorganic fillers, or a combination of both.
[0032] In some embodiments of the present disclosure, the additive is an inorganic filler including BN, Al2O3, AlN, TiO2, SiO2, or a combination thereof. The inorganic filler can reduce the thermal expansion coefficient of the liquid crystal polymer composite layer 120 made of a soluble liquid crystal polymer so that it approaches that of metal, thereby avoiding warping of the laminate. The liquid crystal polymer composition to which the inorganic filler is added can be used in the manufacture of devices such as printed wiring boards. In some embodiments where the additive is an inorganic filler, since the inorganic filler is difficult to dissolve in a solvent, it is necessary to sufficiently and uniformly disperse the inorganic filler particles to obtain a good effect. In some embodiments, the average particle size of the inorganic filler may be selected to be about 20% to about 40%, such as 25%, 30%, or 35%, of the thickness of the liquid crystal polymer composite layer 120. In some embodiments, the particle size of the inorganic filler may be between about 0.1 μm to about 20 μm, such as 0.5 μm, 1 μm, 2 μm, 5 μm, 10 μm, or 15 μm.
[0033] In some embodiments of the present disclosure, the additive of the liquid crystal polymer composition is an organic polymer. The organic polymer may be, for example, a polyester liquid crystal polymer, an aromatic polyester, an aromatic polyamide, polyparaphenylene terephthalamide, polyparaphenylene benzobisoxazole, a copolymer of p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid, or a combination thereof. In some embodiments, the organic polymer is soluble in the solvent of the liquid crystal polymer composition. In other embodiments, the organic polymer is insoluble in the solvent of the liquid crystal polymer composition. By adding an organic polymer to the liquid crystal polymer composition, the thermal expansion coefficient of the liquid crystal polymer composite layer 120 made of the soluble liquid crystal polymer can be reduced, and the situation in which the thermal expansion coefficient is high can be improved, and the thermal expansion coefficient can be made closer to that of metal, thereby avoiding warping of the laminate. In some embodiments, the organic polymer is insoluble in the solvent of the liquid crystal polymer composition, and the average particle size of the organic polymer can be selected to be between about 20% and about 40%, for example, 25%, 30%, or 35%, of the thickness of the liquid crystal polymer composite layer 120. In some embodiments, the particle size of the organic polymer is between about 0.1 μm and about 20 μm, such as 0.5 μm, 1 μm, 2 μm, 5 μm, 10 μm, or 15 μm.
[0034] By adding an organic polymer to the liquid crystal polymer composition, the thermal expansion coefficient of the liquid crystal polymer composite layer 120 manufactured from the liquid crystal polymer composition can be reduced, thereby preventing warping of the laminate. When the organic polymer is added, when the temperature reaches the melting point of the organic polymer and the organic polymer is in a molten state, the orientation of the soluble liquid crystal polymer is changed, and the change in the original thermal expansion coefficient due to the modification of the liquid crystal polymer is reduced. In addition, since the thermal expansion coefficient of organic polymers such as liquid crystal polymers is small, the thermal expansion coefficient can be reduced even by adding the liquid crystal polymer composition.
[0035] In embodiments where the additive is an organic polymer, the liquid crystal polymer composite layer 120 made with the liquid crystal polymer composition is suitable for use in both printed circuit boards and soft copper foil substrates.
[0036] In some embodiments of the present disclosure, the additive may include two or more kinds of inorganic fillers or two or more kinds of organic polymers. In some embodiments, the additive may include a combination of inorganic fillers and organic polymers. The additive may also reduce the thermal expansion coefficient of the liquid crystal polymer composite layer 120 made of the liquid crystal polymer composition. Appropriate combinations of additives may be selected according to requirements, and will not be described here.
[0037] If the amount of additive is too low, for example, if the amount of additive is less than 0.5 parts by weight based on 100 parts by weight of soluble liquid crystal polymer, the effect of improving the thermal expansion coefficient becomes unclear. However, if the amount of additive is too high, for example, if the amount of additive is more than 300 parts by weight based on 100 parts by weight of soluble liquid crystal polymer, the properties such as water absorption rate, dielectric constant and gas barrier property of the manufactured liquid crystal polymer composite layer will change significantly, and the merit of the liquid crystal polymer composite layer for manufacturing a laminate with liquid crystal polymer will be lost. In one embodiment of the present disclosure, the amount of additive is about 1 to about 300 parts by weight based on 100 parts by weight of soluble liquid crystal polymer, for example, 5, 10, 25, 50, 100, 150, 200 or 250 parts by weight.
[0038] In an embodiment of the present disclosure, the liquid crystal polymer composition is cyclized at high temperature on the surface of the metal layer 110 by precision coating or precasting to form the liquid crystal polymer composite layer 120. The liquid crystal polymer composite layer 120 and the metal layer 110 constitute a single-sided liquid crystal polymer metal laminate. The temperature of the high temperature cyclization is between about 200°C and about 400°C, for example, 250°C, 300°C, or 350°C. The time of the high temperature cyclization is between about 10 and about 300 minutes, for example, 20 minutes, 50 minutes, 100 minutes, 150 minutes, 200 minutes, or 250 minutes.
[0039] According to the technical solution of the present disclosure, the thermal expansion coefficient of the liquid crystal polymer composite layer 120 formed by the liquid crystal polymer composition can be reduced, more specifically, the thermal expansion coefficient of the liquid crystal polymer composite layer 120 can be reduced to about 12 to 25 ppm within the range of 100 ° C to 200 ° C. Compared with the liquid crystal polymer composite layer 120 not treated by the technical means of the present disclosure, the thermal expansion coefficient is about 28 to 50 ppm. As can be seen, the technical solution adopted in the present disclosure can effectively reduce the thermal expansion coefficient whose range is close to the thermal expansion coefficient of metal. When the thermal expansion coefficients of the liquid crystal polymer composite layer 120 and the metal layer 110 are close, problems such as warping are not easily caused in the laminate, and the service life and application range of the laminate can be extended. In addition, the liquid crystal polymer composition provided by the present disclosure can be used as a precasting molding material.
[0040] In addition, various laminates disclosed in the present disclosure can be combined to form a thick laminate without departing from the spirit of the present disclosure. For example, but not limited to, the liquid crystal polymer composite layer 120 can include two or more layers, and the number of layers, materials, and thickness of one layer can be arbitrarily adjusted according to the design requirements of different thicknesses to match the metal wiring design to be placed on the surface, and have the best ability to withstand high voltage or high current.
[0041] Although this disclosure has described certain embodiments in detail, other embodiments are possible, and therefore, the spirit and scope of the appended claims should not be limited to the embodiments described herein.
[0042] Although the present disclosure has been disclosed above through the embodiments, this does not limit the present disclosure, and a person skilled in the art may make various changes and modifications without departing from the spirit and scope of the present disclosure, and therefore the scope of protection of the present disclosure is based on the content specified in the claims below. [Explanation of symbols]
[0043] 100 Laminate 110 Metal layer 120 Liquid crystal polymer composite layer
Claims
1. A soluble liquid crystal polymer solution containing an additive, the soluble liquid crystal polymer having the following repeating unit structure: 【Chemistry 1】 (Ar is 1,4-phenylene, 1,3-phenylene, 2,6-naphthalene or 4,4'-biphenylene, Y is O or NH, Z is C=O, and X is a carboxyl ester.) the additive contained in the soluble liquid crystal polymer solution containing the additive is polyparaphenylene benzobisoxazole, the additive is dispersed in the solution, and the soluble liquid crystal polymer is dissolved in the solution; The solution contains 100 parts by weight of the soluble liquid crystal polymer and 1 to 300 parts by weight of the additive, When the solution is applied to a substrate to form a liquid crystal polymer composite layer, the solution has a property of reducing the thermal expansion coefficient of the liquid crystal polymer composite layer, The additive-containing soluble liquid crystal polymer solution is characterized in that the average particle size of the polyparaphenylene benzobisoxazole is 20% to 40% of the thickness of the liquid crystal polymer composite layer.
2. The additive-containing soluble liquid crystal polymer solution described in claim 1, wherein the average particle size of the polyparaphenylene benzobisoxazole is 0.1 to 20 μm.
Citation Information
Patent Citations
Material and method for improving dimensional stability of parts and structures constituting precision electronics, optics, photonics, and spacecrafts
JP2003292806A
Liquid-crystal polyester solution composition
JP2004315678A
Film and layered product using the same
JP2006008976A
Method for manufacturing planar heating element, and planar heating element
JP2010165518A
Liquid crystalline polyester composition and electronic circuit board using the same
JP2011032316A